Teor de flúor na água de poços superficiais - Cazotti, Cezar Augusto (2012)
Most of the water supplies in Brasil have a low Fluoride concentration, however there are some places where these concentrations are above the recommended as suitable for human consumption, causing chronicle intoxication, more specifically, dental Fluorosis. This study aimed to know the Fluoride content naturally present in water from 175 shallow wells located in the rural zone of Gabriel Monteiro city, in São Paulo state, in 2004, and to verify if these contents could prevent dental decay. Armed with a map of the city were located and visited all households in which a sample of water used was collected in a polyethylene bottle, then sent to NEPESCO (Collective Health Research Nucleus) laboratory of the Post-Graduation Program of Preventive and Social Dentistry of the Araçatuba Dental School-UNESP, The method used was the Fluoride ion-specific electrode (Orion 9609 BN), coupled to an ion-analyzer (Orion 710 A). The results showed that in 73.36% of the samples in the Fluoride concentrations was considered despicable (< 0.10 ppm F). The Fluoride concentration in water sources do not exceed the values recommended by Brazilian legislation, however, considering the low concentrations of Fluoride found in the sources analyzed, it is important to recommend the use of Fluoride products, if used with proper care, aiming to promote oral health in this population.